Axiological paradigm of social inclusion intensification - selected remarks - Małecka-Łyszczek, Magdalena Iwona; Mędrzycki, Radosław (Review of European and Comparative Law, 2019)
The following paper investigates the values building the axiological paradigm of social inclusion intensification using the legal doctrine. The analysis is set within the Polish legal system, which is part of the international and EU law established for the maintenance of social cohesion. On the one hand, the Polish solutions not only stem from the European civilization heritage, but also create and reinforce it. The individual sections of the paper provide an analysis of such inclusive values as dignity, freedom, equality, common good and social solidarity which are assumed to be the basis for all inclusive actions performed within civil societies in democratic states based on the rule of law. The analysis also considers a possible hierarchy of those values and how they affect each other. While the inclusive values themselves appear to be universal, their relations and influence on each other (possibly: hierarchy) is strictly dependent on the national legislation. The research has shown the way in which the investigated values/principles coexist. Human dignity has been found to be the fundamental and supreme value of the Polish legal system, while social solidarity supports social cohesion. It is not possible to artificially separate those values – only when they intertwine, complete and enhance each other can the inclusive actions be designed and executed in the most advantageous manner. Therefore, values and rules which bear them form a praxeological system; they must be interpreted only within the context of their coexistence, relations and the influence they have on one another. Each of the discussed values takes part in the establishment of the resources shared by a democratic state and by the internal structures of the civil society existing within this state’s bounds. Only by taking them all into consideration can we provide an adequate and comprehensive understanding of inclusivity and achieve its desired model.